Isolated Nasopharyngeal Aspergillosis Caused by A flavus and Associated with Oxalosis - (:unkn) unknown (My University, 2004)
We report a case of isolated nasopharyngeal aspergillosis in a 52-year-old woman with Hashimoto's thyroiditis. We found the nasopharyngeal lesion incidentally while evaluating bilateral cervical lymphadenopathy, which we had discovered during a routine follow-up examination pursuant to the patient's thyroid problem. Biopsy analysis of the nasopharyngeal lesion revealed the presence of a mycelium made up of septate hyphae and associated oxalosis. Mycologic examination confirmed that Aspergillus flavus was the responsible pathogen. No systemic involvement or involvement of other head and neck sites was found. The patient had been exposed to a considerable amount of dust during the construction of her house, and this may have been the precipitating factor in the development of her infection. We treated the patient with a 4-week course of itraconazole. At the end of therapy, she exhibited no evidence of A flavus on physical and mycologic examinations.